ANALYTICAL FRAMEWORK FOR STUDY THE FATWAS OF SHARIA ECONOMICS - Sofian Al Hakim (AHKAM : Jurnal Ilmu Syariah, 2019)
As a legal opinion, fatwas are an important part of the development of the Sharia economics. Islamic values embodied in sharia norms are confirmed in the fatwa. In case of sharia economics, the fatwa itself was determined by scholars who are considered to have scientific authority capable in the field of fiqh muamalah maliyah and Islamic economics. In principle, the fatwa is non-binding. Because, fatwas are legal opinions. However, the fatwa has a binding power when the fatwa is established as the basis for establishing compliance with sharia norms by law. As applied in several countries, such as Malaysia and Indonesia. This fatwa model is an interesting phenomenon to study. In order to conduct an in-depth analysis of the fatwa an analysis framework is needed that can be used as a guide in conducting a study. There are several analytical frameworks prepared by experts to analyze sharia economic fatwas. This article describes the analytical framework adapted from Emitai Etzioni when explaining social change. Fatwas are analyzed by considering the source of the birth of fatwa, the substance which is the content of the fatwa, and the impact of the fatwa on the economy and Islamic finance.